Drivers of the European Union’s Environmental Performance - Stoian, Mirela; Brad, Laura; Zaharia, Alina (Frontiers in Environmental Science, 2022)
The interactions between nature and mankind produce a series of ecological, social, economic, institutional, technological and other types of restrictions, which can alter the development of the future society and Earth. Thus, exploring the influencing factors of environmental performance can contribute to better indicate solutions and gaps in past and current policies, as well as to achieve sustainable development. In this regard, recently, more and more indices are developing for assessing a specific theme which targets sustainability, such as carbon footprint, environmental performance index, and sustainable development index. This study aims to analyze the influencing factors of environmental performance index (EPI) at EU level between 2010 and 2020, once in two years using a panel data model. The results were estimated using the Period Sur effect within the generalized least square method and with the White period within the correlation matrix. The results indicate positive relationships between EPI and the circular material use rate, the eco-innovation index, the percentage of internet users from the total of population, the proportion of seats held by women in national parliaments and with other drivers. Additionally, the GINI Index, the natural resources rents, the trade volume index, and the share of environmental taxes in total tax revenues seem to constrain the EU’s environmental performance.